Associated Conditions of Diabetes Mellitus and Fatty Liver (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The wide prevalence of non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (DM2), as well as their relationship, determines the need for targeted consideration of this pathology in order to optimize approaches to the diagnosis and treatment of patients with NAFLD and type 2 diabetes. Being components of the metabolic syndrome, these two diseases have largely similar mechanisms of development and progression, synergistically increasing the risk of adverse outcomes in comorbid patients. Despite the commonality of pathophysiological mechanisms, the question of the sequence of development of NAFLD and T2DM remains relevant.Based on the results of the analysis of the literature, two main theories were identified: alimentary and metabolic. According to the alimentary theory, the primary link in the pathogenesis is obesity and the associated excessive accumulation of free fatty acids and triglycerides in the liver, which subsequently leads to insulin resistance and the development of type 2 diabetes. In contrast, the metabolic theory considers the insulin resistance associated with diabetes to be the primary blow, which, regardless of obesity, creates the prerequisites for liver damage. In addition, the review pays special attention to the consideration of a new concept - metabolically associated fatty liver disease (MAFLD), considered as a hepatic component of the metabolic syndrome. Within the framework of this concept, various clinical phenotypes of NAFLD are distinguished, which determine the path along which the diseases under consideration develop. In conclusion, the review discusses pathogenetically based therapy, which focuses on overcoming insulin resistance, correcting atherogenic dyslipidemia, and restoring the structure and function of liver cells.